2017
DOI: 10.1155/2017/7021862
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Achilles Tendon Rupture in the Patients with Achilles Tendinopathy: Healthcare Database Analysis in the United States

Abstract: Introduction. Disorders of the Achilles tendon can be broadly classified into acute and chronic entities. Few studies have established chronic Achilles tendinopathy as a precursor to acute Achilles ruptures. In this study, we assessed the relationship between Achilles tendinopathy and rupture, clarifying the incidence of rupture in the setting of underlying tendinopathy. Methods. The United Healthcare Orthopedic Dataset from the PearlDiver Patient Record Database was used to identify patients with ICD-9 codes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 20 publications
3
63
0
1
Order By: Relevance
“…We speculate that ATR in the ESRD population is less attributable to sports and more attributable to other factors such as metabolic abnormality, 21,27 use of fluoroquinolones and steroids, 5,30 lower levels of regular physical activity, 2 or preinjury tendinosis. 14,35…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that ATR in the ESRD population is less attributable to sports and more attributable to other factors such as metabolic abnormality, 21,27 use of fluoroquinolones and steroids, 5,30 lower levels of regular physical activity, 2 or preinjury tendinosis. 14,35…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, disorganization of collagen, increased noncollagenous ECM, hypercellularity, and neovascularization can be seen[ 11 , 12 ]. The exact relationship between tendinopathy and tendon rupture remains unknown, but it has been reported that tendinopathy increases the risk of tendon rupture[ 13 ]. Acute partial or complete tendon rupture interrupts tendon continuity, leading to bleeding, clotting, and the release of PDGF, TGF-β, ATP, and ADP from platelets and of epinephrine and norepinephrine from blood vessels at the wound site[ 9 ], resulting in a decrease or even loss of function and, potentially, in the loss of mobility.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, a rat Achilles tendinopathy used to model hand diseases here might not be suitable since known knowledge demonstrated that Achilles tendon rupture rates were widely and thoroughly acknowledged to be strongly male dominant. USA health care data indicates males sustained ruptures more frequently than females (male versus female; 141 per 100,000 versus 67 per 100,000) [ 31 ]. In a 10-year-period in Sweden of 27,702 patients with acute Achilles tendon ruptures 79% were men (21,979 men) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%